Menstrual Hygiene Knowledge among Adolescents Girls in Rural Rakai District, Uganda - Lubinga, Rachel; Nalugoda, Fred; Nakyanjo, Neema; Babirye, Estellah; Nakazibwe, Tahiya; Oyewande, Christiana; Okoror, Titilayo (APHA., 2017)
There is limited research on menstrual hygiene knowledge among rural adolescents’ girls in Rakai District of Uganda, although research shows that over 57% of girls aged 11-13 absent themselves from school in Uganda due to menstrual-related challenges. It is estimated that about half of the girl pupils miss 1-3 days of school per month, translating into a loss of 8-24 school days per year (approximately 11% of the learning time). This is due largely to lack of menstrual hygiene management support (unpublished data). While the focus of research on menstrual hygiene has been carried out in urban areas, there is a need to examine this issue in rural communities. As part of a larger study on menstrual hygiene management, this study assessed the knowledge level among girls who participated in girls’ training workshops. Methods: In collaboration with the Rakai Health Sciences Program, training workshops on reproductive health and empowerment activities were organized in six different locations across Rakai District rural communities. The decision to organize the workshops was based on prior field work that indicated the challenges adolescent girls were having in managing their menstrual hygiene, and missing school due to these challenges. Announcements about the workshops were made at various schools in the district, and school administrators were provided with flyers to distribute. Workshop Training modules included fundamentals of the female reproductive cycle, such as ‘loving your body as it changes’, maintaining cleanliness, and ‘finding your voice’. Workshops were facilitated by health educators. All the girls completed an assent form for minors, while parents completed consent forms. Participants were then divided into groups of 11-14 years old and 15-17 years old. All participants completed demographic questionnaire, and a 10-item knowledge survey to assess their knowledge, and identify gaps that were then addressed during the workshops. All participants received gift packs that included sanitary pads among other items.244 girls participated in the study. Most participants were 14 to 16 years old (73%). While many reported that menstruation is not a disease (74%), and can cause pain (92%), most responded that pregnant women can menstruate (91%), and menstrual blood comes from the stomach where food is digested (72%). Girls ages 16-17 had a higher average number of correct responses than girls aged 12-15, although this difference was not statistically significant (t=1.89, p=0.06). Average number of correct answers was 2.44. There is a need for health education programs on menstrual hygiene, which is essential in efforts to reduce absenteeism, reproductive tract infections and improve health of adolescent girls.
Keywords: Adolescents Girls; Menstrual Hygiene; Knowledge